New algorithm for analyzing phosphorescence curves: Its application to the K2YF5:Pr compound. (June 2017) - Ortega, F.; Marcazzó, J.; Spano, F.; Santiago, M.; Molina, P.; Caselli, E.
Abstract: Analysis of phosphorescence curves is an alternative procedure to glow curve analysis in order to find the parameters characterizing trap and recombination centers of thermoluminescence materials. In this article a new algorithm to analyze phosphorescence curves is reported, which is derived from the set of coupled differential equation describing the carrier traffic without resorting to approximations. The new algorithm has been employed to analyze the phosphorescence curves of the K2 YF5 :Pr compound. Highlights: Analysis of phosphorescence curves. Novel algorithm derived without approximations. Interaction among traps taken into account.